Indigenous Sport and Nation-Building : Interrogating Sámi Sport and Beyond - Skille, Eivind Å. (Taylor & Francis, 2022)
This book investigates the social, political, and cultural dimensions of Indigenous sport and nation-building. Focusing on the Indigenous Sámi of Norway, Sweden, Finland, and Russia, it addresses how colonization variously impacts organizational arrangements and everyday sporting life in a modern world. Through detailed case data from the Norwegian side of Sápmi (the land of the Sámi), this book provides a critical and contemporary perspective of post-colonial influences and their impacts on sport. The study uses concepts of conventions, citizenship and communities, to examine the tenuous roles of Indigenous-based sport organizations and clubs towards the building of an Indigenous nation. The book further draws together international, national, and local Sámi experiences to address the communal and assimilative influences that sport brings for people in the North Calotte. Taken together, the book signals the importance of sport in future community development and the (re)emergence of Indigenous culture. Appealing to policy makers and scholars alike, the book will be of particular interest to researchers in sport sociology, Indigenous studies and post colonialism. It also provides essential insight for public officials and administrators of sport and/or Indigenous issues at various levels of public office. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.